SOCIAL-HUMANITARIAN SCIENCE – THE RESULT OF THE SOCIAL NEEDS OF A SOCIETY - Davlatov, Oybek G. (International Journal of Psychosocial Rehabilitation, 2020)
v Personality is a unique historical event. A person is a human being who has some kind of spiritual identity. In fact, the image of a nation is shaped by the image of its people. But individuals can play a negative or positive role in the case of a nation. It depends on their cultural level and spirituality. This article scientifically and theoretically analyzes the concepts of personality, the place of the social and humanitarian sciences in its perfection, the factors that determine the development of society, as well as the possibilities of science and education.